Attitudes towards non-standard Malaysian English / Rabi’atul ‘Adawiyah Abdul Razak - Rabi’atul ‘Adawiyah, Abdul Razak (2015)
The use of Standard English has always been important in Malaysia especially in education. However, people start to incorporate the non-standard English in their everyday lives including education. The problem occurs when students start using it in school as they are used to it and the non-standard English, Manglish is not acceptable in education. Education institutions have aålways promote the use of the Standard English and it has been the only variety that is acceptable in our educational context. According to Peter Tan and Daniel Tan (2008), some people have considered the non- standard English as a stepping stone towards Standard English and some still try to keep the non- standard English out of the school context. In this study, 70 students from an International School participated and they have answered questionnaires in order to examine their perceptions as well as their attitudes towards non-standard Malaysian English. Results show students approved of the non-standard Malaysian English being used in their daily lives but it was not appropriate to use it with teachers in school. This paper examines on the attitudes of secondary students in Malaysia towards non-standard English in Malaysia and to observe the students’ reactions towards it in the educational context.